Causal associations between pediatric asthma and united airways disease: a two-sample Mendelian randomization analysis - Gao, Tongxun; Cai, Qiuhan; Hu, Siyuan; Zhu, Rongxin; Wang, Jixuan (Frontiers in Medicine, 2024)
Background: Previous observational studies have suggested a significant association between pediatric asthma and united airways disease (UAD). however, these findings may be influenced by confounding factors and reverse causality. Therefore, our study employs the Mendelian randomization (MR) method to investigate the causal association between pediatric asthma and UAD. Methods: We conducted a comprehensive two-sample Mendelian randomization (MR) analysis to investigate the association between pediatric asthma and seven groups of UAD, including chronic sinusitis, chronic rhinitis, nasopharyngitis and pharyngitis, chronic diseases of tonsils and adenoids, chronic laryngitis and laryngotracheitis, chronic bronchitis, bronchiectasis, chronic obstructive pulmonary disease (COPD). The present study employed a range of methods for two-sample MR analysis, including inverse variance weighted (IVW), MR-Egger regression, Simple mode, weighted median, and weighted models. The conclusion of the MR analysis primarily relies on the IVW results, while other analytical methods are utilized as supplementary evidence to ensure result robustness in this MR analysis. And sensitivity analyses were conducted, including heterogeneity test, horizontal pleiotropy test, MR-PRESSO test, and leave-one-out analysis to validate the results. Results: The results of the MR analysis indicate significant causal effects of pediatric asthma on chronic rhinitis, nasopharyngitis and pharyngitis (IVW: OR = 1.15, 95%CI: 1.05-1.26, p-value = 0.003), chronic diseases of tonsils and adenoids (IVW: OR = 1.07, 95%CI: 1.00-1.15, p-value = 0.038), chronic bronchitis (IVW: OR = 1.51, 95%CI: 1.42-1.62, p-value <0 .001), bronchiectasis (IVW: OR = 1.51, 95%CI: (1.30-1.75), p-value <0.001), and COPD (IVW: OR = 1.43, 95%CI: 1.34 -1.51, p-value <0.001). However, no significant causal association was observed between pediatric asthma and chronic sinusitis (IVW: OR = 1.00, 95%CI: 1.00-1.00, p-value = 0.085), chronic laryngitis and laryngotracheitis (IVW: OR = 1.05, 95%CI: 0.90-1.21, p-value = 0.558). Conclusion: Our findings support a potential causal relationship between pediatric asthma and UAD, suggesting that pediatric asthma may be a potential risk factor for various UAD.